2017
DOI: 10.1016/j.ijrobp.2017.06.2088
|View full text |Cite
|
Sign up to set email alerts
|

Distinctions Between the Metabolic Changes in Glioblastoma Cells and Glioma Stem-like Cells Following Irradiation

Abstract: Local tumor ablation can be achieved by physical energy-based therapies, such as, irradiation, ultrasound, microwave and radiofrequency. Although tumor antigens released from ablated tumors could induce an anti-tumoral immunity, antigen presentation from ablated tumors are not efficient in inducing a strong systemic immunity. Recently, we demonstrated that immunopriming by LOFU, followed by hypofractionated radiation, reversed immunological tolerance of T cells in draining lymph nodes, induced systemic anti-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…GSCs have been reported to express cell surface CSCs markers, such as stage-specific mouse embryonic antigen, CD34, CD44, α6- integrin, CD133, L1CAM (L1 Cell Adhesion Molecule), CD54, and A2B5 [ 97 , 217 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 ]; cytoskeleton proteins (also referred as; intermediate filaments or nanofilaments), such as glial fibrillary acidic protein (GFAP) [ 236 ], vimentin [ 237 , 238 , 239 ], and Nestin; transcription factors, such as SOX2, Nanog, Oct3/4 [ 240 , 241 ], nuclear factor erythroid 2-related factor 2 (Nrf2) [ 241 , 242 ], oligodendrocyte transcription factor (Olig2) [ 243 ], FoxM1 [ 244 ], and zinc finger protein 281 (ZNF281) [ 245 ], POU class 3 Homeobox 2 [ 246 ], and melanocyte inducing transcription factor (MITF) [ 247 ]; posttranscriptional factors, such as Musashi 1 [ 248 ] and microRNAs [ 249 ]; polycomb (Pc) transcriptional suppressors, such as enhancer of zeste homolog 2 and BMI 1 [ 248 ]; transcriptional co-activators, such as YAP/TAZ [ 171 ] and TRRAP [ 250 ], yet no single marker is able to define a general GSC population. It has been reported that GSCs metabolism undergoes different changes than that of traditional GBM tumor cells following IR [ 251 ]. Gene expression analyses of GBM cells treated by IR have revealed that many genes are modulated after treatment [ 252 , 253 , 254 ].…”
Section: Cancer Stem Cells Concept History and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…GSCs have been reported to express cell surface CSCs markers, such as stage-specific mouse embryonic antigen, CD34, CD44, α6- integrin, CD133, L1CAM (L1 Cell Adhesion Molecule), CD54, and A2B5 [ 97 , 217 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 ]; cytoskeleton proteins (also referred as; intermediate filaments or nanofilaments), such as glial fibrillary acidic protein (GFAP) [ 236 ], vimentin [ 237 , 238 , 239 ], and Nestin; transcription factors, such as SOX2, Nanog, Oct3/4 [ 240 , 241 ], nuclear factor erythroid 2-related factor 2 (Nrf2) [ 241 , 242 ], oligodendrocyte transcription factor (Olig2) [ 243 ], FoxM1 [ 244 ], and zinc finger protein 281 (ZNF281) [ 245 ], POU class 3 Homeobox 2 [ 246 ], and melanocyte inducing transcription factor (MITF) [ 247 ]; posttranscriptional factors, such as Musashi 1 [ 248 ] and microRNAs [ 249 ]; polycomb (Pc) transcriptional suppressors, such as enhancer of zeste homolog 2 and BMI 1 [ 248 ]; transcriptional co-activators, such as YAP/TAZ [ 171 ] and TRRAP [ 250 ], yet no single marker is able to define a general GSC population. It has been reported that GSCs metabolism undergoes different changes than that of traditional GBM tumor cells following IR [ 251 ]. Gene expression analyses of GBM cells treated by IR have revealed that many genes are modulated after treatment [ 252 , 253 , 254 ].…”
Section: Cancer Stem Cells Concept History and Propertiesmentioning
confidence: 99%
“…After repairing the cellular damage, the cells may re-enter the cell cycle upon stimulation by specific growth factors, such as E2F and CDK2 [ 463 ]. It has been shown that, after IR, GSCs are more quiescent than GBM cells that express elevated levels of glycolysis and oxidative phosphorylation, the so-called “Warburg effect”, whereas GSCs show metabolic signs of quiescence, such as a diminished non-essential amino-acid synthesis, and unchanged levels of glycolytic and oxidative metabolites [ 251 ]. Earlier studies have demonstrated that Ras-related C3 botulinum toxin substrate 2 induces aberrant proliferation of quiescent NSCLC after IR exposure to a single dose of 2 Gy via promoting JUN-B expression through megakaryoblastic leukemia 1—serum response factor (MAL-SRF) pathway [ 464 ].…”
Section: Radiation-induced Dormancymentioning
confidence: 99%
“…It has been said that what doesn't kill you makes you stronger, and in certain respects GBM exemplifies such adaptive behavior. Tumors adapt to radiation-induced oxidative stress through several mechanisms, including metabolic shifts ( 63 ), elevated antioxidant peptide production, and intra-tumoral hypoxia generation ( 150 , 151 ).…”
Section: Effects Of Radiation Therapy On the Gbm Microenvironmentmentioning
confidence: 99%